Comparative study of biofuel and biodiesel blend with mineral diesel using one-dimensional simulation - Rafidah, Rahim; R., Mamat; Mohd Yusof, Taib (IOP Publishing, 2012)
This study is intended to perform one-dimensional simulation for four cylinders diesel engine by using various type of fuels and blend. The testing of biofuels properties conducted according to ASTM standards. The physical properties of the fuel are investigated in chemical laboratory which comprises of flash point, kinematic viscosity, density, cloud & pour point, acid value and moisture content. There are three types of fuels used throughout the study, which are straight vegetable oil (SVO), biodiesel 20% blend (B20) and biodiesel 5% blend (B5). Then, the properties data from the experiment will be used in the simulation GT Power software. Simulation tests have been run with the aim of obtaining comparative measures of torque, power, specific fuel consumption and volumetric efficiency. The results is use to evaluate and analyze the performance of diesel engine running with the mentioned fuels above. The comparison performances for each fuel have been discussed. There is no significant difference in the engine performance when fueled with B5 and diesel. There is only about one percent lower of B5 and four percent higher of B20 and SVO compare to diesel fuel.